Effects of combined estrogen and progesterone replacement treatment on detrusor contractility and histology in oophorectomized rats - (:unkn) unknown (WILEY, 2011)
Aim: The aim of this study was to investigate the effects of estrogen plus progesterone treatment administered after surgical menopause on morphological and muscarinic receptor sensitivity in detrusor muscle bands of rats. Materials and Methods: A total of 40 female Albino-Wistar rats were assigned into two groups to undergo surgical menopause with sham operation (n = 10) and bilateral oophorectomy (n = 30). Thirty oophorectomized rats were assigned into three groups for different treatments administered for 8 weeks beginning from the 7th postoperative day. At the end of the 8th postoperative week, laparotomy was performed in all of them and the urinary bladders were excised and investigated with light microscope. All statistical analysis and graphs were performed using GraphPad Prism version 4. P < 0.05 was considered to be statistically significant. Results: It was determined that average bodyweights were increased to some extent in oophorectomized and sham groups after treatment and while it was more marked in the group receiving estrogen therapy, bodyweights were decreased in the group receiving estrogen plus progesterone therapy. However, this was not statistically significant. No statistically significant difference was determined between the sham, placebo and 17-beta estradiol treatment groups regarding contractile response of urinary bladder tapes to carbachol (P > 0.05). Contractile responses of urinary bladder tapes of the estrogen plus progesterone treatment group were found to be statistically lower than the placebo group (P < 0.05). Conclusion: Our in vitro findings demonstrate that treatment with estrogen plus progesterone decreases muscarinic activity in oophorectomized rats, whereas estrogen-only treatment does not. Our study establishes the basis for further studies to answer whether combination of estrogen and progesterone treatment can restore detrusor overactivity associated with sex hormone defects seen at menopause.
Keywords: detrusor contractility; estrogen; menopause; oophorectomized rats; progesterone; SMOOTH-MUSCLE; OVARIECTOMY; BLADDER; RECEPTORS; ESTRADIOL